Off‐flavour compounds in collagen peptides from fish: Formation, detection and removal. (23rd July 2022) - Wang, Xilong; Le, Bei; Zhang, Na; Bak, Kathrine H.; Zhang, Yuhao; Fu, Yu
Summary: Collagen peptides from fish exhibit excellent bioactive and functional properties, which have great potential as functional ingredients in the food industry. However, the off‐flavour in collagen peptides from fish limits their comprehensive application in the food industry. Therefore, removing the off‐flavour from collagen peptides is of great importance. In this regard, this review firstly recaps the formation mechanism of main off‐flavour compounds of collagen peptides from fish. Furthermore, the main detection methods for off‐flavour compounds are described. More importantly, the removal methods of off‐flavour compounds in collagen peptides derived from fish, such as physical, chemical, biotechnological and combination methods, are emphatically reviewed. In addition, the current challenges and future perspectives are discussed. The present work provides a theoretical reference for removal of collagen peptides from fish. Abstract : Summary of major methods for removal of fishy off‐flavor compounds